2018
DOI: 10.1016/j.jhydrol.2018.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Semianalytical solutions for contaminant transport under variable velocity field in a coastal aquifer

Abstract: Existing closed-form solutions of contaminant transport problems are limited by the mathematically convenient assumption of uniform flow. These solutions cannot be used to investigate contaminant transport in coastal aquifers where seawater intrusion induces a variable velocity field. An adaptation of the Fourier-Galerkin method is introduced to obtain semianalytical solutions for contaminant transport in a confined coastal aquifer in which the saltwater wedge is in equilibrium with a freshwater discharge flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…Similar to other existing 2‐D semianalytical solutions, we take the dispersion tensor as isotropic and constant. Kalejaiye and Cardoso () and Koohbor et al () showed that this assumption is valid when gravity is the main driving force and Rayleigh number is less than 1,000. Both conditions hold in our study.…”
Section: Problem and Model Statementmentioning
confidence: 99%
“…Similar to other existing 2‐D semianalytical solutions, we take the dispersion tensor as isotropic and constant. Kalejaiye and Cardoso () and Koohbor et al () showed that this assumption is valid when gravity is the main driving force and Rayleigh number is less than 1,000. Both conditions hold in our study.…”
Section: Problem and Model Statementmentioning
confidence: 99%
“…The 3‐D semianalytical solution is developed using the FS method also called Fourier‐Galerkin method (Peyret, 2013). This method has been used to obtain semianalytical solutions for several 2‐D density‐driven flow problems (Fahs et al, 2014, 2015, 2016; Henry, 1964; Koohbor et al, 2018; Segol, 1994; Shao, Fahs, Younes, & Makradi, 2016; Shao, Fahs, Younes, Makradi, et al, 2016; Simpson & Clement, 2003, 2004; van Reeuwijk et al, 2009; Younes & Fahs, 2014, 2015; Zidane et al, 2012). Shao et al (2018) extended the FS method to solve a three‐dimensional solute density‐driven flow problem.…”
Section: The Fs Solutionmentioning
confidence: 99%
“…With the development of economy of human society, a myriad of coastal hydrogeological, engineering, biochemical, ecological and environmental problems arise. The problems include, for instance, seawater invasion, land subsidence, engineering structures stability and marine environment deterioration [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Among them, the environmental pollution caused by aquaculture is more serious, which is related to the formation of red tide [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the laboratory experiment, analytical solution and numerical simulation were used to solve the problem of contamination migration in coastal zones [ 8 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The experimental method has been applied earlier to resolve the problem of pollutant migration in coastal aquifer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation